A Cognitive Radio Approach to Realize Coexistence Optimized Wireless Automation Systems - Ahmad, Kaleem; Meier, Uwe; Kwasnicka, Halina; Pape, Andreas; Griese, Bjoern (14th IEEE Conference on Emerging Technologies and Factory Automation - ETFA 2009, Mallorca, Spain)
The need for multiple radio systems in overlapping regions of a factory floor introduces a coexistence problem. The current research challenge is to design and realize radio systems that should be able to achieve a desired quality of service (QoS) in harsh, time-varying, coexisting industrial environments. As a solution cognitive radio (CR) built on top of a reconfigurable platform like software defined radio (SDR) can provide the required system properties. We provide a literature survey about existing coexistence problems and solutions and implement a CR testbed for experimental investigations. It can exploit three dimensions of the hyperspace, which are frequency, time, and transmission power. This CR testbed is investigated in the coexistence of typical radio systems. The experimental results show satisfactory robustness against any of these interferers.